Utilization of Social Media as Information Media: Analysis of Twitter @perpusnas1 - Saleh, Amin; Rifaid, Rifaid (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
The purpose of this study was to analyze the use of social media as a medium of information via Twitter by analyzing National Library of Indonesia accounts1; then, this study used a descriptive qualitative method using secondary data. Social twitter and literature review. The results of this study reveal that disseminating information through social media Twitter with the social media account @perpusnas1 functions as a reliable medium for maintaining literacy communication with users on other platforms. In addition, Twitter and other forms of social media provide a platform for information dissemination. Account intensity is also used to determine how @perpusnas carry out information distribution operations. The @perpusnas1 account has a total tweet intensity of 8,932 tweets, making it an account with a reasonably active information dissemination intensity. The account also has several followers who follow it to spread information through other forms of social media. A report on Twitter that collaborates with several pieces to disseminate information, such as the @gramediadotcom account, aims to increase its users' digital literacy because this account is the most extensive online bookstore account in Indonesia. Then the @ArsipNasionalRI account is an official account controlled by the ANRI Planning and Public Relations Bureau. @kemendikbudRI, and finally, the @naralanguage account, which accounts for speaker service providers in Indonesia. In the context of forming a national archive, management of information related to ANRI operations, products, and policies.